Taking Sleeping Pills and the Risk of Chronic Kidney Disease: A Nationwide Population-Based Retrospective Cohort Study - Liao, Chen-Yi; Chung, Chi-Hsiang; Lu, Kuo-Cheng; Cheng, Cheng-Yi; Yang, Sung-Sen; Chien, Wu-Chien; Wu, Chia-Chao (Frontiers in Pharmacology, 2021)
Background Sleeping disorder has been associated with chronic kidney disease (CKD); however, the correlation between sleeping pills use and CKD has not been investigated in depth yet. This study elucidated the potential association of sleeping pill use with the risk of CKD and CKD progression to end-stage renal disease (ESRD) requiring dialysis. Methods This study was based on a population-based cohort that included 209,755 sleeping pill users among 989,753 individuals. After applying the exclusion criteria, 186,654 sleeping pill users and 373,308 non-users were enrolled to monitor the occurrence of CKD. By using a cumulative daily dose, we analyzed the types of sleeping pills related to the risk of CKD and ESRD. Propensity score matching and analysis using Cox proportional hazards regression were performed with adjustments for sex, age, and comorbidities. Results Sleeping pill use was related to increased CKD risk after adjusting for underlying comorbidities (adjusted hazard ratio [aHR] = 1.806, 95% confidence interval [CI]: 1.617–-2.105, p < 0.001). With the exception of hyperlipidemia, most comorbidities correlated with an increased risk of CKD. Persistent use of sleeping pills after CKD diagnosis increased the risk of concurrent ESRD (aHR = 7.542, 95% CI: 4.267–-10.156, p < 0.001). After the subgroup analysis for sleeping pill use, brotizolam (p=0.046), chlordiazepoxide (p <0.001), clonazepam (p <0.001), diazepam (p<0.001), dormicum (p<0.001), estazolam (p <0.001), fludiazepam (p <0.001), flunitrazepam (p <0.001), nitrazepam (p <0.001), trazodone (p <0.001), zolpidem (p <0.001), zopiclone (p <0.001) were found to have significant correlation with increased CKD risk. Conclusions Sleeping pill use was related to increased risk of CKD and ESRD. Further studies are necessary to corroborate these findings.